Fungus and it’s implication to building performance (School Building) / Mohd Amirul Abdul Aziz - Abdul Aziz, Mohd Amirul (Faculty of Architecture, Planning and Surveying, 2009)
The presence of various types of building with different shapes and construction material such as timber and concrete offers a unique habitat for the growth and development of plants like fungus on the building. Some of the plants are wild species and the rest are species that is planted around the building but spread to the building structures. Different species will give a different effect to the structure because of its physical form such as roots, trunks and leaves and also its ability to retain some amount of water or moisture within its body or at the building structure itself. The species such as Fungus places significant forces to the structure due to its roots and has the ability to penetrate the small cracks and holes on the structure and eventually damages the structure. The knowledge about building maintenance in this regard is very important especially during the diagnosing and building analysis works. The understanding about the growth of plants on building will help integrate the planning and implementation of maintenance work.